Cholangiocarcinoma with respect to IgG4 Reaction - Kenichi Harada; Yasuni Nakanuma (International Journal of Hepatology)
IgG4 reactions marked by infiltration of IgG4-positive plasma cells in affected organs occur in cancer patients and in patients with IgG4-related diseases. Extrahepatic cholangiocarcinomas including gall bladder cancer are often accompanied by significant IgG4 reactions; these reactions show a negative correlation with CD8-positive cytotoxic T cells, suggesting that the evasion of immune surveillance is associated with cytotoxic T cells. The regulatory cytokine IL-10 may induce IgG4-positive plasma cell differentiation or promote B cell switching to IgG4 in the presence of IL-4. Cholangiocarcinoma cells may function as nonprofessional antigen presenting cells that indirectly induce IgG4 reactions via the IL-10-producing cells and/or these may act as Foxp3-positive and IL-10-producing cells that directly induce IgG4 reactions. Moreover, IgG4-related disease is a high-risk factor for cancer development; IgG4-related sclerosing cholangitis (IgG4-SC) cases associated with cholangiocarcinoma or its precursor lesion biliary intraepithelial neoplasia (BilIN) have been reported. IgG4-positive cell infiltration is an important finding of IgG4-SC but is not a histological hallmark of IgG4-SC. For the diagnosis of IgG4-SC, its differentiation from cholangiocarcinoma remains important.